Influences of ageing parameters on the microstructure and mechanical properties of extruded 6063 and 6005 alloys - Do Van Quang; Le Thi Van Anh; Vu Thi Huong Ly; Nguyen Quoc Tuan (Vietnam Journal of Science, Technology and Engineering)
The influences of ageing time and ageing temperature on the microstructure and mechanical properties were investigated for the extruded 6063 and 6005 alloys. Artificial ageing was performed on the alloy extrusions. The ageing process for 6063 aluminium alloy extrusions was studied at temperatures of 190, 205, and 220oC for durations of 90, 150, and 210 minutes, while extruded 6005 alloys were treated at temperatures of 150, 175, and 200oC for 4, 8, and 12 hours. The results demonstrate that the coarse AlMeSi particles formed during extrusion evolved from granular to rod-like particles (AlFeSi) as the ageing temperature or time increased for both aluminium alloy extrusions, with spherical particles (Al(Mn,Cr,Mg)Si) observed in the 6005 aluminium alloy extrusions. The mechanical properties of the extrusions at room temperature were highly sensitive to the ageing process. The optimal tensile strength, elongation, and hardness for the extruded 6063 and 6005 alloys were achieved at 190oC after 150 minutes and at 175oC after 8 hours, respectively.